2022
DOI: 10.1093/pnasnexus/pgac144
|View full text |Cite
|
Sign up to set email alerts
|

Measuring racial and ethnic disparities in traffic enforcement with large-scale telematics data

Abstract: Past studies have found that racial and ethnic minorities are more likely than white drivers to be pulled over by the police for alleged traffic infractions, including a combination of speeding and equipment violations. It has been difficult, though, to measure the extent to which these disparities stem from discriminatory enforcement rather than from differences in offense rates. Here, in the context of speeding enforcement, we address this challenge by leveraging a novel source of telematics data, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, Beckett et al (36) found that the geographic concentration of police resources in Seattle led to higher arrest rates for Black individuals delivering drugs compared to white individuals delivering drugswhere the true racial distribution of those delivering drugs was estimated from survey data and ethnographic observations. Similarly, Cai et al (37) found that the issuance of speeding tickets varied across neighborhoods even after adjusting for the true underlying incidence of speeding, as estimated by the movement of mobile phones.…”
Section: A Statistical Condition For Excluding Featuresmentioning
confidence: 94%
“…For example, Beckett et al (36) found that the geographic concentration of police resources in Seattle led to higher arrest rates for Black individuals delivering drugs compared to white individuals delivering drugswhere the true racial distribution of those delivering drugs was estimated from survey data and ethnographic observations. Similarly, Cai et al (37) found that the issuance of speeding tickets varied across neighborhoods even after adjusting for the true underlying incidence of speeding, as estimated by the movement of mobile phones.…”
Section: A Statistical Condition For Excluding Featuresmentioning
confidence: 94%
“…Academic research generally agrees that racial profiling exists and is widespread ( 7 10 ), though there may be variation between differently sized police departments ( 9 ). In general, research has supported the “minority threat” hypothesis, which suggests that a greater proportion of minority residents in a city is associated with greater policing activity.…”
mentioning
confidence: 99%
“…In general, research has supported the “minority threat” hypothesis, which suggests that a greater proportion of minority residents in a city is associated with greater policing activity. This has resulted in areas with more Black residents experiencing higher ( 8 , 11 ) and growing enforcement rates ( 12 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation